On me demande de développer et de réduire f(x):
f(x)=(x^2-9)-2(x-3)(x+2)
J'ai fais:
f(x)=(x^2-9)-2(x-3)(x+2)
=(x+3)^2-2(x^2+2x-3x-6)
=(x^2-2*x*3-3^2)-(2x^2+4x-6x-12)
=x^2+2x^2+6x+9+4x-6x-12
=3x^2+6x-6x+4x+9-12
=3x^2-4x-3
Vous pouvez me corriger?=d

2

Réponses

2013-09-17T16:59:46+02:00
f(x)=(x^2-9)-2(x-3)(x+2)
   =x^2-9-2(x^2+2x-3x-6)
   =x^-9-2(x^2-x-6)
   =x^2-9-2x^2+4x+12
   =x^2-2x^2+4x-9+12
   =-x^2+4x+3
2013-09-17T17:25:42+02:00
F(x)=(x^2-9)-2(x-3)(x+2)
   =x^2-9-2(x^2+2x-3x-6)
   =x^-9-2(x^2-x-6)
   =x^2-9-2x^2+4x+12
   =x^2-2x^2+4x-9+12
   =-x^2+4x+3